DETERMINAN INTEGRITAS LAPORAN KEUANGAN (Studi Pada Perusahaan Yang Mengikuti Program Corporate Governance Preception Index Tahun 2011-2014) - Puji Novia Kurniawati, 12.05.52.0069; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the influence of corporate governance, independence, audit quality and size of the integrity of the financial statements on the companys corporate governance program preception CGPI index in 2011-2014. The population is all companies follow corporate governance program preception CGPI index in 2011-2014. The sample in this study as many as 70 companies. The sampling technique used purposive sampling. The analytical tool used is a linear regression analysis. The results of the analysis can be concluded that: Corporate governance perception index positive and significant impact on the integrity of financial statements. The independence is not significant positive effect on the integrity of financial statements. Quality audits significant positive effect on the integrity of financial statements. Size companies significant positive effect on the integrity of financial statements.Â  Â Keywords: GCG, Independence, Audit Quality, Size and Integrity of Financial Statements